Characterization of Differentially Abundant Proteins Among Leishmania (Viannia) braziliensis Strains Isolated From Atypical or Typical Lesions - Esteves, Bárbara B.; Melo-Braga, Marcella N.; Gorshkov, Vladimir; Verano-Braga, Thiago; Larsen, Martin R.; Gontijo, Célia M. F.; Quaresma, Patricia F.; Andrade, Helida M. (Frontiers in Cellular and Infection Microbiology, 2022)
Leishmania (Viannia) braziliensis is the main etiological agent of cutaneous and mucocutaneous leishmaniasis in Latin America. Non-ulcerated atypical tegumentary leishmaniasis cases caused by L. braziliensis have been reported in several regions of the American continent, including the Xacriabá indigenous reserve in São João das Missões/Minas Gerais, Brazil. Parasites isolated from these atypical clinical lesions are resistant to antimony-based therapeutics. In the present study, proteins displaying differential abundance in two strains of L. braziliensis isolated from patients with atypical lesions compared with four strains isolated from patients with typical lesions were identified using a quantitative proteomics approach based on tandem mass tag labeling (TMT) and mass spectrometry. A total of 532 (P<0.05) differentially abundant proteins were identified (298 upregulated and 234 downregulated) in strains from atypical lesions compared to strains from typical lesions. Prominent positively regulated proteins in atypical strains included those that may confer greater survival inside macrophages, proteins related to antimony resistance, and proteins associated with higher peroxidase activity. Additionally, we identified proteins showing potential as new drug and vaccine targets. Our findings contribute to the characterization of these intriguing L. braziliensis strains and provide a novel perspective on Atypical Cutaneous Leishmaniasis (ACL) cases that have been associated with therapeutic failures.